Multidimensional inequality in Vietnam, 2002-2012 - Thi Kim Thanh Bui; Guido Erreygers (Economies, 2020)
We investigate the evolution of multidimensional inequality of well-being in Vietnam in the period 2002-2012 using household survey data. Our study focuses on four crucial dimensions of human welfare: consumption, education, health and housing. We measure inequality by means of the multidimensional Atkinson index, which belongs to the Atkinson family of relative inequality indices. The choice of the values of two crucial parameters, with respect to the aversion to inequality on the one hand and the degree of substitutability between dimensions on the other hand, has a significant influence on the perceived trends of inequality. We consider different combinations of dimensions (two, three and four dimensions) and a wide variety of values of the parameters, with the aim of arriving at a robust understanding of the extent of inequality in Vietnam. Our results suggest that the level of multidimensional inequality in Vietnam has decreased, albeit that this is not the case for all combinations of the parameter values. Our study shows that looking at multidimensional rather than one-dimensional inequality leads to a richer understanding of the evolution of inequality, and indicates that it is important to be aware of the influence of value judgments on the assessment of inequality.
Keywords: 330; Vietnam; Atkinson index; multidimensional inequality